2003
DOI: 10.1016/s0044-8486(02)00572-0
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of sex in two ZZ pseudofemale lines of tilapia Oreochromis aureus

Abstract: This paper reports a study on the sex determination system of the blue tilapia, Oreochromis aureus. Investigations were carried out using a pseudofemale line in two populations of O. aureus, known as Egyptian Population (EP) and Israel Population (IP). In O. aureus, males are the homogametic sex (ZZ/ZW), and sex reversal of fry with estradiol results in the production of some functional sexreversed fish with a female phenotype and ZZ male genotype, known as pseudofemales or D-females. Crosses between ZZ pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…This study, as well as those of Hopkins (1979) and Mélard (1995), demonstrated male homogamety for this species. A monofactorial sex determination system with two sex chromosomes (WZ) in O. aureus was also supported by results from the analysis of progeny sex ratios from pseudofemales (Desprez et al, 2003), who showed that it is possible to obtain high proportions of male progeny from successive generations of pseudofemales by hormonal sex reversal and progeny testing.…”
Section: Introductionmentioning
confidence: 86%
“…This study, as well as those of Hopkins (1979) and Mélard (1995), demonstrated male homogamety for this species. A monofactorial sex determination system with two sex chromosomes (WZ) in O. aureus was also supported by results from the analysis of progeny sex ratios from pseudofemales (Desprez et al, 2003), who showed that it is possible to obtain high proportions of male progeny from successive generations of pseudofemales by hormonal sex reversal and progeny testing.…”
Section: Introductionmentioning
confidence: 86%
“…The hypothesis of a differential mortality of certain genotypes, suggested by Jalabert et al (1971) and Chen (1969), cannot be excluded. Moreover, as demonstrated by Shirak et al (2002) in an inbred Table 4 Number and percentage of crosses giving each sex-ratio (h : U) in theory of Avtalion and Hammerman (1978) (Mair et al, 1997;Desprez et al, 2003a). These recent studies have demonstrated that male genetic sex determining factors (sex chromosomes, autosomal factors) can be fixed in a line of breeders.…”
Section: Discussionmentioning
confidence: 96%
“…To explain unpredicted results in Oreochromis, which are not consistent with a monofactorial sex chromosomes model, a more complex system was proposed by adding a further genetic sex determining/regulating locus, the autosomal recessive gene (F,f) to the major bsex chromosomesQ (Wohlfarth and Wedekind, 1991;Mair et al, 1991a,b;Trombka and Avtalion, 1993;Desprez et al, 2003a). Crossingover and recombination of sex determining genes could also account for these unpredicted sex-ratios (Mair et al, 1991a,b;Mü ller-Belecke and Hö rstgenSchwark, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations